Manajemen Sumber Daya Manusia: Unggul, Kreatif, dan Inovatif di Era Revolusi Industri 4.0 - R. Sabrina (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
Human Resource Management (HRM) during the current covid-19 pandemic must be carried out optimally. Maximum management can have a positive effect for the realization of the goal of reaching the peak of expectations in line with the current period. Therefore, the urgency of research on human resource management is needed. The purpose of this study is to determine the superior, creative, and innovative HRM in the education and organizational sector. This research method uses a qualitative approach, with the type of literature review research. The data sources used are secondary data sources by reviewing articles in journals and secondary data from books to support this research, all of which are in accordance with the research objectives or research relevance. The result of the research is that HRM can be carried out in a superior, creative, and innovative way, so that management objectives can be achieved and are effective in the activities carried out. Excellent in managing human resources, creative in activating activities, and innovative in finding ideas.